Evaluasi Penerapan Saluran Informasi dan Penanganan Pengaduan (SIPP) bagi Peserta BPJS Kesehatan - Sri Lestari Ramadhani Nasution; Muhammad Rinaldy; Ermi Girsang (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study evaluates the application of Information Channels and Complaint Handling (SIPP) for BPJS Health participants at Sawit Indah Perbaungan Public Hospital. The research method uses in-depth interviews. There were nine informants in this study consisting of 5 BPJS participants and four informants who were Sawit Indah Perbaungan Public Hospital employees. The study results indicate that the usual obstacle Sawit Indah Perbaungan Hospital faces in implementing SIPP is the length of response or answers to the effects of complaints from BPJS participants who use the SIPP complaint service caused by the network. The benefit felt by BPJS Health participants with SIPP is that it is more effective in submitting complaints. In conclusion, overall, the application of SIPP for BPJS Health participants at Sawit Indah Perbaungan Public Hospital has been running effectively. Keywords: Health BPJS, Information Channels, and Complaint Handling